When the Aims and the Ends of Health Care Misalign. (February 2022) - Berry, Leonard L.; Attai, Deanna J.; Scammon, Debra L.; Awdish, Rana Lee Adawi
In health care, a high-emotion service, unintended consequences can be especially problematic. People's physical, psychological, and financial well-being—even their lives—are at stake. As scientific, technological, and demographic changes make health care a much more complex service to deliver, efforts to anticipate, avoid, and correct unintended consequences become more crucial. Using narrative examples and an extensive review of the data and the literature, we explore these efforts in four domains of U.S. health care: (1) the increasingly widespread, often challenging use of electronic health records; (2) the threat to the patient-clinician relationship from a greater, sometimes narrow emphasis on productivity metrics; (3) the culture of medicine's frequently misguided prioritizing of treatment over true healing; and (4) the overreliance on family caregivers who are often poorly prepared to care for the seriously ill. We then apply lessons from health care's unintended consequences to non-health-care services and suggest opportunities for service researchers to contribute to improving health care delivery, a service that all of us need.